Migration of a Swallowed Blunt Foreign Body to the Neck - Kerem Ozturk; Goksel Turhal; Sercan Gode; Atilla Yavuzer (Case Reports in Otolaryngology)
Ingestion of foreign bodies is a common problem in the otolaryngology practice. Reports of extraluminal migration of the foreign bodies from the upper aerodigestive tract are rare. Penetration and extraluminal migration of ingested foreign bodies may cause severe vascular and suppurative complications, even death. We report a 4-year-old girl who presented with a mass and partial extrusion of a foreign body in the neck. She had a history of ingesting the plastic top piece of a knitting needle approximately 1 year ago. She had been asymptomatic until the present time. The examination revealed a red, blunt, rectangular plastic foreign body half embedded in the skin of the right neck. Esophagography with barium swallow, cervical X-rays, and computed tomography scans were obtained. The foreign body was easily removed under general anesthesia. Primary closure and direct laryngoscopy was also performed. The patient recovered very well without any complications.